53.9k views
2 votes
10. Two students' solutions to the equation 6(x+4)3x-2 are shown. Both students made an error. Find the errors.

Student 1
6(x+ 4) = 3x - 2
*+43x-2-6
** 43x-
*+4+3x-88
x+12 3x
12 - 2x
Student 2
6(x + 4) = 3x - 2
6x + 43x-2
3x + 4 =-2
3x + 4-4--2-4
3x = -6
X-2
X
6X
T

1 Answer

0 votes

Answer:

5x² - 13x + 71

Explanation:

We are to subtract 3x²+7x-43 from 8x²-6x+28

That is:

8x² - 6x + 28 - (3x² + 7x - 43)

8x² - 6x + 28 - 3x² - 7x + 43

Collect like terms:

8x² - 3x² - 6x - 7x + 28 + 43

5x² - 13x + 71

User Juju
by
5.8k points